A comparative evaluation of antioxidant enzymes and selenium in the serum of periodontitis patients with diabetes mellitus type 2 - Biju Thomas; Amitha Ramesh; Sneha Suresh; B Rajendra Prasad (Wolters Kluwer Medknow Publications, 2013)
Context: Chronic periodontitis is an inflammatory disease with an aberrant response characterized by exaggerated inflammation, involving the release of excess proteolytic enzymes and reactive oxygen species (ROS). Diabetes mellitus is a group of complex multisystem metabolic disorders characterized by a relative or absolute insufficiency of insulin secretion and or concomitant resistance to the metabolic action of insulin on target tissues. Increased production of ROS necessitates elevated requirements for the nutrients involved in antioxidant defenses: Selenium, zinc, and copper. Inflammatory states promote a decrease in the amount of systemic glutathione levels. Catalase is a central antioxidant enzyme constituting the primary defense against oxidative stress. Aims: This study has been designed to evaluate the comparison of glutathione, catalase, and selenium levels in the serum of diabetes mellitus type 2 patients and healthy individuals with and without periodontal disease. Settings and Design: This study is a case control study. Materials and Methods: The study was designed as a case - control study comprising of 150 subjects, inclusive of both sexes and were divided into three groups of 50 patients each. Group I: 50 subjects with type 2 diabetes mellitus and chronic periodontitis. Group II: 50 subjects who are systemically healthy with the chronic periodontitis. Group III: 50 subjects who are systemically healthy and not suffering from Periodontitis: Serum samples were taken for estimation of glutathione, catalase, and selenium from all groups, and Subjected to biochemical analysis after which atomic absorption spectrophotometry method was used to obtain their levels in serum. Statistical Analysis Used: ANOVA and Tukey HSD. Results: The serum levels of glutathione in diabetic patients with periodontitis were significantly lower with a mean of 61.36 + 8.054 when compared to healthy individuals with and without periodontitis with a mean of 56.93 + 6.874 and 90.36 + 6.564 respectively (P ≤ 0.005). The serum levels of catalase were significantly lower in diabetic patients with periodontitis with a mean of 19.30 + 7.355 when compared to healthy individuals with and without periodontitis with a mean of 20.71 + 6.472 and 36.09 + 5.108 respectively ( P ≤ 0.005). The serum levels of selenium were significantly lower in diabetic patients with periodontitis with a mean of 81.41 + 55.419 when compared to healthy individuals with and without periodontitis with a mean of 161.44 + 84.787 and 193.84 + 66.713 respectively (P ≤ 0.005). Conclusions: The findings from the study suggest that the levels of glutathione, catalase, and selenium are significantly lower in diabetic patients with periodontitis and also in healthy individuals with periodontitis, but are highest in healthy controls, showing that the serum levels are inversely proportional to inflammation and tissue destruction.